2015
DOI: 10.1021/cb5008647
|View full text |Cite
|
Sign up to set email alerts
|

N-Myristoyltransferase Is a Cell Wall Target in Aspergillus fumigatus

Abstract: Treatment of filamentous fungal infections relies on a limited repertoire of antifungal agents. Compounds possessing novel modes of action are urgently required. N-myristoylation is a ubiquitous modification of eukaryotic proteins. The enzyme N-myristoyltransferase (NMT) has been considered a potential therapeutic target in protozoa and yeasts. Here, we show that the filamentous fungal pathogen Aspergillus fumigatus possesses an active NMT enzyme that is essential for survival. Surprisingly, partial repression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
53
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(57 citation statements)
references
References 60 publications
3
53
0
1
Order By: Relevance
“…Several studies have investigated the biology and pathogenesis of NMT from malaria and leishmania within its potential as a novel drug target by exploiting the inhibition effect observed when NMT expression is disrupted (Banerjee, Arora, & Murty, ; Bell et al., ; Brannigan et al., ; Tate, Bell, Rackham, & Wright, ). Furthermore, recognition of NMT as a cell wall target of Aspergillus fumigatus infection has also identified NMT as a potential therapeutic drug target (Fang et al., ; Valiante, Macheleidt, Foge, & Brakhage, ), and NMT has been identified as a novel antifungal target of Candida albicans (Sikorski et al., ; Wiegand et al., ). A study of the role of NMT in relation to human immunodeficiency virus proteins has revealed that the myristoylation of Gag and Nef proteins is a key for viral replication and virulence (Seaton & Smith, ).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have investigated the biology and pathogenesis of NMT from malaria and leishmania within its potential as a novel drug target by exploiting the inhibition effect observed when NMT expression is disrupted (Banerjee, Arora, & Murty, ; Bell et al., ; Brannigan et al., ; Tate, Bell, Rackham, & Wright, ). Furthermore, recognition of NMT as a cell wall target of Aspergillus fumigatus infection has also identified NMT as a potential therapeutic drug target (Fang et al., ; Valiante, Macheleidt, Foge, & Brakhage, ), and NMT has been identified as a novel antifungal target of Candida albicans (Sikorski et al., ; Wiegand et al., ). A study of the role of NMT in relation to human immunodeficiency virus proteins has revealed that the myristoylation of Gag and Nef proteins is a key for viral replication and virulence (Seaton & Smith, ).…”
Section: Introductionmentioning
confidence: 99%
“…This irreversible modification is catalyzed by myristoyl-CoA:protein N-myristoyltransferase (NMT), an enzyme present in all organisms that have been examined to date, from yeast to humans. Because the modification is required for the correct function of substrate proteins, NMTs are essential for viability in organisms including the fungi C. albicans (Lodge et al , 1994b), A. fumigatus (Fang et al , 2015), and C. neoformans (Lodge et al , 1994a). Biochemical and structural analyses of NMTs suggest that they are potential therapeutic targets for diseases ranging from cancers to parasitic and fungal infections (Georgopapadakou, 2002; Panethymitaki et al , 2006; Das et al , 2012).…”
Section: Overview Of Lipid Modifications Of Proteinmentioning
confidence: 99%
“…Their occurrence in pathogenic microbes had been relatively unexplored, until recent reports detailing lipid modifications of proteins from bacteria (Hicks and Galan, 2013; Ivanov and Roy, 2013), parasites (Goldston et al , 2014), and fungi. The last group includes medically important organisms such as Candida albicans (Richard et al , 2002; Piispanen et al , 2011), Aspergillus fumigatus (Fontaine et al , 2003; Fortwendel et al , 2012; Fang et al , 2015), and Cryptococcus neoformans (Selvig et al , 2013; Nichols et al , 2015; Santiago-Tirado et al , 2015). …”
Section: Introductionmentioning
confidence: 99%
“…13) NMT participates in membrane targeting and the function of many proteins in a variety of signal transduction cascades and other critical cellular functions. 14) Moreover, NMTs are striking in their remarkable diversity of peptide substrates and diversity in the peptidebinding groove has offered potential of developing speciesspecific inhibitors. 14) As a result, NMT has been identified as a potential chemotherapeutic target enzyme for antifungal agents.…”
Section: Synthesis Characterization and Antifungal Evaluation Of Novmentioning
confidence: 99%
“…14) Moreover, NMTs are striking in their remarkable diversity of peptide substrates and diversity in the peptidebinding groove has offered potential of developing speciesspecific inhibitors. 14) As a result, NMT has been identified as a potential chemotherapeutic target enzyme for antifungal agents. 1) Previously, Sheng and colleagues 12) had prepared tetrahydrocarbazole derivatives ( Fig.…”
Section: Synthesis Characterization and Antifungal Evaluation Of Novmentioning
confidence: 99%